The identification of talent in soccer - a brief review - Focan, G.; Paraschiv, C.; Zamfir, C. M. (Revista Romaneasca pentru Educatie Multidimensionala, 2018)
In this review, we intended to identify and provide the most important overview of research in talent identification in soccer and highlighting information for those who are interested into future research in this field. Some peer-reviewed empirical articles were collected and analyzed. The literature reveals considerable evidence demonstrating that 8 indicators must be taken into consideration in talent assessment: maturation, physiological abilities, technical skills, tactical skills, psychosocial attributes, deliberate practice, genetic factors and the context.